Penerapan Manajemen Layanan Karir di Madrasah Aliyah Negeri - Islamiati, Zuha Nur; Suardiman, Siti Partini; Suyatno (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Career service management is a critical element in helping students plan their futures. This research aims to explore and understand career service management at Madrasah Aliyah Negeri in Sleman, focusing on the stages of planning, implementation, and evaluation of career programs. Additionally, this study examines the factors that influence students’ career goal-setting, including the roles of parents, teachers, and industry partnerships. A qualitative descriptive approach was employed, with data collected through field observations and structured interviews with the school principal, vice-principals, career guidance counselors, and several students. The results indicate that career service management at MAN Sleman is conducted systematically through collaboration between the school, parents, and external partners such as industry professionals. Parental support and guidance from career counselors significantly affect students in choosing careers that align with their interests and abilities. Career programs, including workshops, industrial visits, and individual counseling, were successfully implemented, although some challenges remain in the evaluation process, particularly regarding students' anxiety in career decision-making. This research contributes to the development of more effective career services in schools and serves as a reference for other institutions seeking to improve their career services to better meet students’ needs.